Infection surveillance after a natural disaster: lessons learnt from the Great East Japan Earthquake of 2011 - Osuke Iwata; Tomoharu Oki; Aiko Ishiki; Masaaki Shimanuki; Toru Fuchimukai; Toru Chosa; Shoichi Chida; Yasuhide Nakamura; Hiroji Shima; Michihiro Kanno; Toyojiro Matsuishi; Mikihito Ishiki; et al. (The World Health Organization, 2013)
Problem On 11 March 2011, the Great East Japan Earthquake produced a catastrophic tsunami that devastated the city of Rikuzen-Takata and left it without an effective health infrastructure and at increased risk of outbreaks of disease. Approach On 2 May 2011, a disease-surveillance team was formed of volunteers who were clinicians or members of Rikuzen-Takata's municipal government. The team's main goal was to detect the early signs of disease outbreaks. Local setting Seven weeks after the tsunami, 16 support teams were providing primary health care in Rikuzen-Takata but the chain of command between them was poor and 70% of the city's surviving citizens remained in evacuation centres. The communication tools that were available were generally inadequate. Relevant changes The surveillance team collected data from the city's clinics by using a simple reporting form that could be completed without adding greatly to the workloads of clinicians. The summary findings were reported daily to clinics. The team also collaborated with public health nurses in rebuilding communication networks. Public health nurses alerted evacuation centres to epidemics of communicable disease. Lessons learnt Modern health-care systems are highly vulnerable to the loss of advanced technological tools. The initiation - or re-establishment - of disease surveillance following a natural disaster can therefore prove challenging even in a developed country. Surveillance should be promptly initiated after a disaster by (i) developing a surveillance system that is tailored to the local setting, (ii) establishing a support team network, and (iii) integrating the resources that remain - or soon become - locally available.